EFEKTIVITAS KONSUMSI TABLET Fe SELAMA MENSTRUASI TERHADAP PENINGKATAN KADAR HAEMOGLOBINPADA SISWI SMAN 3 KOTA PALU - Luciana Luciana; Hasnidar Hasnidar; Maharani Farah Dhifa Dg. Masikki (STIKes CHMK, 2019)
Menstruation is the release of the uterine wall (endometrium) which is accompanied by bleeding and occurs every month unless it is pregnant. Lots of blood coming out plays a role in the occurrence of anemia because women do not have enough supplies of Fe and absorbs of Fe into the body cannot replace the loss of Fe during menstruation. To anticipate iron anemia is by giving iron tablets, education and related efforts to remember iron intake through food, control of infectious diseases, and fortification of staple foods with iron. The research objective was to know the effectiveness of consumption of Fe tablets during menstruation on the increase in hemoglobin levels in female students of SMAN 3 in Palu City. The research design used was Pre experimental, with pre-test and post-test one group desion, a population of 606 students and a sample of 61 female students who menstruated at SMAN 3 Palu. Using the research instrument observation sheet. The independent variable is the administration of Fe tablets and the dependent variable which is an increase in hemoglobin levels during menstruation. Data analysis using statistical test paired t-test, significant value α α 0.005. The results showed that there was an effect of consumption of Fe tablets during menstruation on an increase in hemoglobin levels in female students of SMAN 3 Palu City with a value of p value = 0,000. The conclusion of this study is that there is an effect on the effectiveness of consumption of Fe tablets during menstruation on the increase in hemoglobin levels in female students of SMAN 3 Kota Palu. It is recommended for respondents to know the magnitude of the benefits of giving added blood tablets so that they can increase the level of Hb especially in young women who are experiencing menstruation. Keywords: Hemoglobin Levels, Fe Tablets, Menstruation.